Layered NiFe-LDH/MXene nanocomposite electrode for high-performance supercapacitor - Zhou, Hua; Wu, Fang; Fang, Liang; Hu, Jia; Luo, Haijun; Guan, Ting; Hu, BaoShan; Zhou, Miao (International journal of hydrogen energy, 2020)
Layered double hydroxide (LDH) is potentially excellent supercapacitor (SC) materials, but the low conductivity and easy agglomeration limit the further improvement of their electrochemical properties. Therefore, LDHs are requisite to grow on some conductive substrates to produce high-performance SC. In this paper, the conductive two-dimensional (2D) transition metal carbides, nitrides and carbonitrides (called MXene) were explored as the substrate to directly deposit NiFe-LDH nanosheets by a one-step hydrothermal method, then a three-dimensional (3D) porous NiFe-LDH/MXene electrode was obtained. The morphology and electrochemical performance of the composite electrodes were analyzed and investigated. The results show that the NiFe-LDH/MXene electrode has larger specific capacitance (720.2 F/g) than NiFe-LDH (465 F/g), and the capacitance of the composite electrode retained 86% after 1000 cycles (only 24% for NiFe-LDH), showing excellent cycle stability. The improved electrochemical performance of the composites is caused by the stable sheet-like structure of NiFe-LDH during charge-discharge time and the conductive network formed by the MXene, which can accelerates electron transport. In addition, the asymmetric SC based on NiFe-LDH/MXene positive electrode display a power density of 758.27 W/kg at an energy density of 42.4 Wh/Kg. These results indicate the NiFe-LDH/MXene composites can be applied as the novel candidate of high-performance SC electrodes. •The LDH/MXene synergistic hybrid structure is developed with MXene nanosheets as the substrate.•Prominent electrical performance is attributed to MXene providing a fast charge transfer path for LDH.•The anchoring of LDH on MXene surface provides the material with enhanced cyclic stability.